Biguanides inhibit complex I, II and IV of rat liver mitochondria and modify their functional properties - Drahota, Z; Palenickova, E; Endlicher, R; Milerova, M; Brejchova, J; Vosahlikova, M; Svoboda, P; Kazdova, L; Kalous, M; Cervinkova, Z; Cahova, M (Physiological research, 2014)
In this study, we focused on an analysis of biguanides effects on mitochondrial enzyme activities, mitochondrial membrane potential and membrane permeability transition pore function. We used phenformin, which is more efficient than metformin, and evaluated its effect on rat liver mitochondria and isolated hepatocytes. In contrast to previously published data, we found that phenformin, after a 5 min pre-incubation, dose-dependently inhibits not only mitochondrial complex I but also complex II and IV activity in isolated mitochondria. The enzymes complexes inhibition is paralleled by the decreased respiratory control index and mitochondrial membrane potential. Direct measurements of mitochondrial swelling revealed that phenformin increases the resistance of the permeability transition pore to Ca(2+) ions. Our data might be in agreement with the hypothesis of Schäfer (1976) that binding of biguanides to membrane phospholipids alters membrane properties in a non-specific manner and, subsequently, different enzyme activities are modified via lipid phase. However, our measurements of anisotropy of fluorescence of hydrophobic membrane probe diphenylhexatriene have not shown a measurable effect of membrane fluidity with the 1 mM concentration of phenformin that strongly inhibited complex I activity. Our data therefore suggest that biguanides could be considered as agents with high efficacy but low specifity.
Keywords: biguanidy; respirační komplex I; Electron Transport Complex II; Phenformin; Male; Rats, Wistar; Mitochondria, Liver; vztah mezi dávkou a účinkem léčiva; respirační komplex IV; mužské pohlaví; Enzyme Inhibitors; potkani Wistar; respirační komplex II; Electron Transport Complex IV; krysa rodu Rattus; jaterní mitochondrie; metformin; Animals; zvířata; Rats; Biguanides; Metformin; Electron Transport Complex I; fenformin; Dose-Response Relationship, Drug; inhibitory enzymů